Dora the Explorer. Dora's first trip - Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2006)
Dora tells the story of how she first met Boots. Includes 4 episodes.
Dora's first trip -- Best friends -- Tree house -- Chocolate tree.
Title from container.
Special features: "Best friends" music video.
MPAA rating: Not rated.
DVD, region 1, full screen presentation ; Dolby Digital stereo., NTSC.
English and Spanish or French dialogue; closed-captioned.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile drama; Adventure and adventurers -- Juvenile drama; Friendship -- Juvenile drama; Dora the Explorer (Fictitious character) -- Juvenile drama; Adventure and adventurers -- Juvenile drama; Friendship -- Juvenile drama; Dora the Explorer (Fictitious character) -- Drama; Adventure and adventurers -- Drama; Friendship -- Drama; Dora the Explorer (Personaje literario) -- Teatro juvenil; Aventuras -- Teatro juvenil; Amistad -- Teatro juvenil; Films for the hearing impaired; Children's -- Animation -- Television series